Integrating fish farming and agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Present systems of farming will not meet the projected food needs for most ACP countries in the twenty-first century. Where sufficient water is available and soils are suitably water retentive, the integration of aquaculture with agriculture could...